Optimal protein requirement for rapid and coordinated test growth of juvenile sea urchin (Strongylocentrotus intermedius) - Panke Gong; Haijing Liu; Dan Gou; Weixiao Di; Huinan Zuo; Jun Ding; Yaqing Chang; Rantao Zuo (Aquaculture Reports)
Rapid and coordinated test (the main part of shell) growth is crucial for maintaining the normal body shape of juvenile sea urchin (Strongylocentrotus intermedius). However, imbalanced growth of the test height (TH) and test diameter (TD) of S. intermedius frequently occurs when they are fed formulated feeds. In this study, a 90-days satiety feeding experiment was performed to investigate the effects of different protein levels on the feed intake, somatic growth, and test characteristics of juvenile S. intermedius. Fresh kelp (Saccharina japonica) (control diet) and five formulated feeds with graded levels of protein (5 %, 10 %, 15 %, 20 %, and 25 %) were used as experimental diets, which were named kelp, P5, P10, P15, P20, P25 groups. Each diet was randomly allocated to three cages of sea urchins (initial body weight: 1.23 ± 0.01 g). The results indicated that feed intake gradually decreased as dietary protein increased. The weight gain rate of S. intermedius in the P10 group was comparable to that in the P5 and P15 groups but was significantly higher than that in the P20 and P25 groups. The test height growth rate of S. intermedius in the P5 group was comparable to that in the P10 and P15 groups but was still lower than that in the kelp group. The TH/TD of S. intermedius in the P5 group was comparable to that in the P10 and kelp groups but was significantly greater than that in the P15, P20, P25 groups. S. intermedius in the P5 group showed the closest test microstructure to those in the kelp group, characterized by larger holes, longer but thinner trabeculae, as well as more regular microstructure in both outer and side surfaces, and more active resorption of inner test surface. These results indicated that S. intermedius fed diets with 5 % protein had fastest growth of TH and most balanced TH/TD, which could be due to the increased test construction efficiency by speeding up test resorption, increasing hole diameter and trabecula length, and decreasing trabecula width. It was recommended that the dietary protein level should be no more than 10 % for achieving rapid and coordinated growth of juvenile S. intermedius.